A Survey on the Organization and Operation of Level II/III Neonatal Intensive Care Units in Greece: A Comparison Between 2004 and 2022 - Kosmas Sarafidis; Nicoletta Iacovidou; Eleftheria Hatzidaki; Ilias Chatziioannidis; Gabriel Dimitriou (Children)
Background/Objectives: Limited data exist on the organization and operation of Level II/III Neonatal Intensive Care Units (NICUs) in Greece; this retrospective cross-sectional survey explored their structure and functioning in 2004 and 2022. Methods: A structured questionnaire was utilized, along with demographic and perinatal data obtained from the Hellenic Statistical Authority. Results: Between 2004 and 2022, live births decreased by 28%, while the prematurity rate rose from 6.96% to 11.87% (p < 0.001). Significant regional differences were observed in the number of NICUs (p = 0.033), live births (p < 0.001), and NICUs per 10,000 live births (p = 0.025). In this survey, data from 20 Level III NICUs in 2004 and 22 NICUs (one Level II) in 2022 were analyzed. NICU admissions increased by 16.1% (p = 0.389), while the rate of admitted neonates/1000 live births increased from 13.5 to 21.8 (p < 0.001). In 2022, premature infants constituted 40.2% of NICU admissions. The number of board-certified neonatologists increased by 21.8% between 2004 and 2022 (p = 0.795), along with a rise in the ratio of neonatologists per 10,000 live births (from 14.8 to 25, respectively, p < 0.001). Conversely, there was a significant 17.2% reduction in the nursing staff by 2022 (p = 0.034). The number of available NICU beds also increased during the study period. The ratio of ventilators to intensive care beds significantly improved (p < 0.001). In 2022, new treatment modalities, like therapeutic hypothermia, were introduced, and most NICUs reported offering long-term follow-up programs. Conclusions: This survey highlights significant advancements in Level II/III NICU infrastructure and care capabilities, while emphasizing demographic changes and a critical shortage of neonatal nursing staff. These factors should be carefully considered by health authorities in the development of future neonatal care strategic planning in the country.